Synthesis and characterization of new bromomolybdate complex (C6H13)4N MoO3Br (Bangladesh Journal of Scientific and Industrial Research, 2015)
The reaction between tetrahexylammonium bromide and MoO3 produced a new bromo salt (bromotrioxomolybdate (VI)). (C6H13)4N [MoO3Br], characterized by IR, UV/Visible and 81Br-NMR techniques.Bangladesh J. Sci. Ind. Res. 50(4), 297-299, 2015